Keberadaan Candida Albicans Dengan Sanitasi Toilet Umum Di Pasar Tradisional Kota Bekasi Tahun 2017 - WIDYASTUTI, ARNI; RIYANTO, AGUS (BULLET : Jurnal Multidisiplin Ilmu, 2023)
Traders and visitors of traditional have an effect on the condition of public toilet sanitation in the market. The condition of public toilet sanitation in Indonesia is inadequate, bacteria and microorganisms are still widely found, especially microorganisms that can and are accustomed to living in human skin. Toilet condition is not sanitary will facilitate the growth of bacteria, viruses, fungi such as Candida albicans. This study aims to determine the condition of public toilet sanitation and the presence of Candida albicans in a public toilet water reservoir in a traditional market in Bekasi City in 2017. This research is a descriptive cross sectional research. Sanitation conditions were carried out by observation and the presence of Candida Albicans was performed through laboratory analysis. The results showed that 2 of 4 traditional markets included in this study identified the existence of Candida Albicans. Sanitation conditions 1 of 4 traditional markets in Kota Bekasi indicate sanitary conditions that toilet condition is not sanitary. In addition, the behavior of officers in the public toilets in 2 of the 4 markets shows uncare conditions in the public toilet.